Protein Arginine Methyltransferase 1‐Dependent Labeling and Isolation of Histone H4 through N‐Mustard Analogues of S‐Adenosyl‐l‐methionine. (9th January 2019) - Hymbaugh, Sarah J.; Pecor, Lindsay M.; Tracy, Christopher M.; Comstock, Lindsay R.
Abstract: Histones, the fundamental building blocks of nucleosomes, undergo post‐translational modifications and play a major role in the regulation of transcriptional processes. Although the significance of these modifications, including methylation, is widely recognized, little is known about the mechanisms connecting such events. To improve our understanding of how protein methylation is intricately linked, we have developed novel N ‐mustard analogues of S ‐adenosyl‐l ‐methionine (SAM) functionalized with azides and alkynes to serve as probes of biological methylation. Here, we demonstrate their ability to serve as effective cofactor mimics of SAM and to be enzymatically transferred by protein arginine methyltransferase 1 (PRMT1) to histone H4 with high site selectively for its target Arg3 on the histone tail. Further incorporation of biotin through copper‐catalyzed click chemistry permitted visualization and isolation of the analogue‐modified histone H4 from a complex mixture. This work validates the future utility of N ‐mustard analogues as probes of protein methylation events beyond PRMT1. Abstract : Captured : Although the significance of histone post‐translational modifications, including methylation, is widely recognized, little is known about the mechanisms connecting such events. We have developed N ‐mustard analogues of S ‐adenosyl‐l ‐methionine functionalized with azides and alkynes that probe biological methylation by facilitating the isolation of PRMT1‐dependent labeling of histone H4 through chemoselective biotinylation.